Sufistic Meditation as a Form of Happiness Transformation - Naan Naan; Siti Aisyah (el Harakah: Jurnal Budaya Islam, 2023)
This study focuses on the discussion of Sufistic meditation as a form of happiness transformation. A discussion that has long been the subject of study. Happiness itself is the hope of everyone, but in reality, the happiness obtained is only false happiness, not eternal happiness. In Buddhist rituals, meditation is a practice that must be done in any school of Buddhism, and this has been a tradition since time immemorial. In this study, meditation from the Sufism perspective is presented as a method to enhance the transformation of true happiness. Meditation according to Buddhism has the same essence as the ritual practices in Islam, only the terms used vary. In Sufism, meditation has a word equivalent to the terms mentioned in Islam, namely Dhikr, tafakkur, mujahadah, muraqobah, riyadhah, and uzlah. In addition, the concept of happiness from several perspectives is also discussed, such as happiness from the perspective of Western psychology, happiness from the Sufistic perspective, and happiness according to experts. The author uses this topic as a study to further explore that Islam also has meditation methods with its perspective, and this Sufistic-based meditation is very supportive to improve the transformation of our spirituality in general and happiness in particular. Kajian ini memfokuskan pada pembahasan tentang meditasi sufistik sebagai bentuk transformasi kebahagiaan. Suatu pembahasan yang sudah lama menjadi bahan kajian. Sebagaimana kebahagiaan itu sendiri menjadi harapan setiap orang, tetapi pada kenyataannya kebahagiaan yang diperoleh hanyalah kebahagiaan yang bersifat semu, bukan kebahagiaan yang abadi. Dalam ritual agama Buddha, meditasi adalah satu praktik yang harus dilakukan dalam aliran Buddhaisme mana pun, dan ini sudah menjadi tradisi sejak dahulu kala. Dalam kajian ini meditasi perspektif tasawuf hadir sebagai metode untuk meningkatkan transformasi kebahagiaan yang sejati. Meditasi menurut agama Buddha memiliki esensi yang sama dengan ritual praktik yang ada dalam agama Islam, hanya saja istilah yang digunakan beragam. Dalam tasawuf, meditasi mempunyai padanan kata dengan istilah yang disebut dalam agama Islam, yaitu Dzikir, tafakkur, mujahadah, muraqobah, riyadhah, dan uzlah. Selain itu, juga dibahas konsep kebahagiaan dari beberapa perspektif, seperti kebahagiaan perspektif psikologi barat, kebahagiaan perspektif sufistik, dan kebahagiaan menurut para ahli. Topik ini penulis jadikan sebagai kajian pembahasan guna mengeksplorasi lebih jauh bahwa Islam juga mempunyai metode meditasi dengan perspektifnya sendiri, dan meditasi berbasis sufistik ini sangat mendukung untuk meningkatkan transformasi spititualitas kita umumnya dan kebahagiaan khususnya.